MAKNA ISTILAH TEKNIS DALAM NOVEL SERIAL BEDEBAH KARYA TERE LIYE - Wardati, Jeri; Patriantoro, Patriantoro; Wartiningsih, Agus (Jurnal Kajian Pembelajaran dan Keilmuan, 2023)
This study aims to describe the meaning of technical terms in Tere Liye's serial novel Bedebah, and to find out the implementation of linguistic elements in stories (novels) learning Indonesian at high school behavior. The research method used is a descriptive method with a qualitative research form. The data source for this research is the serial novel Bedebah by Tere Liye. Data collection techniques and tools used in this research were observation and note taking techniques and the researchers themselves. Data analysis techniques used are data collection, data reduction, data presentation, drawing conclusions. The results of this study are about technical terms in the Bedebah serial novel by Tere Liye. The classification results of the meaning of technical terms in Tere Liye's Bedebah serial novels cover various fields of study, such as political science, physics, law, biology, economics, automotive, sociology, military, psychology, geography, medicine, chemistry, arts. The semantic meaning of technical terms is analyzed based on lexical meaning, grammatical meaning, and contextual meaning